Molecular mechanisms involved in secretory vesicle recruitment to the plasma membrane in β-cells. (April 2002) - Varadi, A.; Ainscow, E. K.; Allan, V. J.; Rutter, G. A.
Abstract : Glucose stimulates the release of insulin in part by activating the recruitment of secretory vesicles to the cell surface. While this movement is known to be microtubule-dependent, the molecular motors involved are undefined. Active kinesin was found to be essential for vesicle translocation in live β-cells, since microinjection of cDNA encoding dominant-negative KHC mut (motor domain of kinesin heavy chain containing a Thr 93 → Asn point mutation) blocked vesicular movements. Moreover, expression of KHC mut strongly inhibited the sustained, but not acute, stimulation of secretion by glucose. Thus, vesicles released during the first phase of insulin secretion exist largely within a translocation-independent pool. Kinesin-driven anterograde movement of vesicles is then necessary for the sustained (second phase) of insulin release. Kinesin may, therefore, represent a novel target for increases in intracellular ATP concentrations in response to elevated extracellular glucose and may be involved in the ATP-sensitive K + channel-independent stimulation of secretion by the sugar.